Two Worlds Colliding: The Interplay Between Natural Compounds and Non-Coding Transcripts in Cancer Therapy - Alexandru A. Sabo; Maria Dudau; Maria Dudau; George L. Constantin; Tudor C. Pop; Christoph-M. Geilfus; Alessio Naccarati; Alessio Naccarati; Mihnea P. Dragomir (Frontiers Media S.A., 2021)
Cancer is a devastating disease and has recently become the leading cause of death in western countries, representing an immense public health burden. When it comes to cancer treatment, chemotherapy is one of the main pillars, especially for advanced stage tumors. Over the years, natural compounds have emerged as one of the most valuable resources for new chemotherapies. It is estimated that more than half of the currently used chemotherapeutic agents are derived from natural compounds. Usually, natural compounds are discovered empirically and an important limitation of introducing new anti-cancer natural products is lack of knowledge with regard to their mechanism of action. Recent data has proven that several natural compounds may function via modulating the expression and function of non-coding RNAs (ncRNAs). NcRNAs are a heterogenous class of RNA molecules which are usually not translated into proteins but have an important role in gene expression regulation and are involved in multiple tumorigenic processes, including response/resistance to pharmacotherapy. In this review, we will discuss how natural compounds function via ncRNAs while summarizing the available data regarding their effects on over 15 types of cancer. Moreover, we will critically analyze the current advances and limitations in understanding the way natural compounds exert these health-promoting effects by acting on ncRNAs. Finally, we will propose several hypotheses that may open new avenues and perspectives regarding the interaction between natural compounds and ncRNAs, which could lead to improved natural compound-based therapeutic strategies in cancer.